2018
DOI: 10.1126/science.aat4191
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously low dielectric constant of confined water

Abstract: The dielectric constant ε of interfacial water has been predicted to be smaller than that of bulk water (ε ≈ 80) because the rotational freedom of water dipoles is expected to decrease near surfaces, yet experimental evidence is lacking. We report local capacitance measurements for water confined between two atomically flat walls separated by various distances down to 1 nanometer. Our experiments reveal the presence of an interfacial layer with vanishingly small polarization such that its out-of-plane ε is onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

65
918
2
11

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 810 publications
(996 citation statements)
references
References 42 publications
(108 reference statements)
65
918
2
11
Order By: Relevance
“…(D)] . Related to this, a recent study showed that in a sub‐nanometer space the dielectric constant of water becomes smaller than 2 along the direction of narrowing; however, the resultant dielectric constant is likely to be anisotropic, and thus this observation is not in conflict with our arguments. In the presence of a crevice and thus of focused E Ψ , a charged group captured inside the creviced protein will sense a powerful electrostatic force, which, due to reduced thickness of the insulating medium ( d < < 3 nm), can become significantly stronger than the 5‐pN value estimated from a uniform E Ψ .…”
Section: Two‐state Rigid‐body Motion Is a Common Way To Utilize Electsupporting
confidence: 59%
“…(D)] . Related to this, a recent study showed that in a sub‐nanometer space the dielectric constant of water becomes smaller than 2 along the direction of narrowing; however, the resultant dielectric constant is likely to be anisotropic, and thus this observation is not in conflict with our arguments. In the presence of a crevice and thus of focused E Ψ , a charged group captured inside the creviced protein will sense a powerful electrostatic force, which, due to reduced thickness of the insulating medium ( d < < 3 nm), can become significantly stronger than the 5‐pN value estimated from a uniform E Ψ .…”
Section: Two‐state Rigid‐body Motion Is a Common Way To Utilize Electsupporting
confidence: 59%
“…The current work is also motivated by recent atomic force microscope (AFM) studies on the quasi‐liquid layer at ice surfaces and the anomalous dielectric properties of the nano‐scale water . In these experimental studies, the AFM tip near the water surface was served as an electrode, therefore, the strength of the electric field between the electrode surface and water surface depends on the applied voltage on the AFM tip and there should exit strong correlation between the charge fluctuation on the metal surface and the thermal capillary fluctuation for the dipolar water surfaces.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The current state‐of‐the‐art nanotechnology has created numerous approaches to generate confined space on the nanoscale to reinvestigate various physicochemical phenomenon 1. For examples, the dielectric constant of water confined in channels with distance down to 1 nm decreases from ≈80 for bulk water to ≈2, because of the restricted rotational freedom of water dipoles near surfaces 2. Moreover, the water molecules confined in inter‐nanoparticles gaps show ice‐like structure at room temperature 3.…”
Section: Introductionmentioning
confidence: 99%